Interrupting the internal clock: DIscriminability and break location effects - MENEZ, MARINA; LÓPEZ, FLORENTE (Mexican Journal of Behavior Analysis, 2011)
Continuous memory decay and instructional ambiguity hypotheses are different explanations for reset and stop-retain timing strategies of the internal clock. For the memory decay hypothesis, stop-retain and reset represent the edges of memory decay. The instructional ambiguity hypothesis sustains that the clock operation mode is the result of a failure to discriminate between the inter trial interval (ITI) and the break. In addition, both hypotheses suggest that the current conditions at the moment of introducing the break are involved in the operation of the internal clock. These explanations were tested in two groups of rats. Break location and similarity of ITI and break duration were manipulated. Findings indicated that similarity between ITI and break duration, as was here manipulated, does not induce reset of the internal clock. Break location yielded shifts in peak time as predicted by the memory decay hypothesis. An alternative explanation in terms of current response rate at the moment of the introduction of the break, was proposed.